PENGARUH MEDIA PAPAN MINIATUR HITUNG TERHADAPPENINGKATAN KEMAMPUAN MATHEMATIC LOGIC SISWAKELAS 3 DI SDN IV SUKAMURNI - Abdul Mugni; Husnul Rahmi (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study aims to determine the effect of miniature counting board media on the Mathematical Logic abilities of 3rd grade students in mathematics learning at SDN IV Sukamurni. By using quantitative descriptive methods, experimental methods and one group pretest-posttest design. The population used was all students of SDN Sukamurni IV Cilawu consisting of three lower classes with a total of 81 students. The sampling technique used in this study used the Nonprobability Purposive Sampling method, namely one class as a sample taken with a total of 24 students. The first meeting was carried out pretest and the second meeting until the sixth meeting was given learning using the Miniature Counting Board media with the material of multiplication arithmetic operations. At the seventh meeting students were given posting questions to determine students' Mathematical Logic abilities after being given the Miniature Counting Board media. Data obtained from the posting results were used to test the research hypothesis using the Spearman Rho test and regression. From the results obtained p count is smaller than 0.010 p table 0.05, it can be said that between variables X (implementation of miniature counting board media) and Y (mathematical logic ability) there is a significant relationship based on hypothesis testing with the magnitude of the relationship r = 0.523 with a coefficient of determination of 27.35%. Furthermore, a regression test analysis was carried out to obtain a significant-f obtained smaller than alpha 0.05 or (0.141 < 0.05). so it can be concluded that there is an effect of the application of Miniature Counting Board media on improving Mathematical Logic abilities in grade 3 students in mathematics learning at SDN Sukamurni IV Cilawu. While the regression equation is Y = 25.073 + 0.358X.